2021
DOI: 10.1177/09514848211028707
|View full text |Cite
|
Sign up to set email alerts
|

Hospital complications among older adults: Better processes could reduce the risk of delirium

Abstract: Using observational data and variation in hospital admissions across days of the week, we examined the association between ED boarding time and development of delirium within 72 hours of admission among patients aged 65+ years admitted to an inpatient neurology ward. We exploited a natural experiment created by potentially exogenous variation in boarding time across days of the week because of competition for the neurology floor beds. Using proportional hazard models adjusting for socio-demographic and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Data are contingent upon evaluations and documentation by clinicians, mainly in bedside encounters; thus, ascertainment is neither systematic nor random 39. Not all staff from hospital floors documented observed delirium symptoms, calculated CAM scores or even screened high-risk patients (ie, older adults with acute ischemic stroke) 13. Not all physicians screened for or documented cognitive changes in the medical record; in fact, hypoactive delirium cases could be frequently undiagnosed 9.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data are contingent upon evaluations and documentation by clinicians, mainly in bedside encounters; thus, ascertainment is neither systematic nor random 39. Not all staff from hospital floors documented observed delirium symptoms, calculated CAM scores or even screened high-risk patients (ie, older adults with acute ischemic stroke) 13. Not all physicians screened for or documented cognitive changes in the medical record; in fact, hypoactive delirium cases could be frequently undiagnosed 9.…”
Section: Discussionmentioning
confidence: 99%
“…Because delirium disproportionately affects older adults, its associated morbidity, mortality, and costs are projected to increase with population aging 10. However, informed policy and population health management are contingent upon the reliable ascertainment of disease status and health care utilization for persons with delirium 11–13…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ED itself may be a culprit in precipitating delirium. ED lengths of stay exceeding 10 hours are associated with incident delirium among hospitalized older adults, 24 and patients with neurologic emergencies arriving to the ED on a day of high boarding are more likely to develop delirium 25 . Another observational study demonstrated that the absence of mobilization during the whole ED length of stay was independently associated with a 3‐fold odds of incident delirium 26 …”
mentioning
confidence: 99%
“…ED lengths of stay exceeding 10 hours are associated with incident delirium among hospitalized older adults, 24 and patients with neurologic emergencies arriving to the ED on a day of high boarding are more likely to develop delirium. 25 Another observational study demonstrated that the absence of mobilization during the whole ED length of stay was independently associated with a 3-fold odds of incident delirium. 26 With ED boarding at crisis levels in this country and no indication of abatement, 27 we cannot continue pushing off delirium and mobility initiatives to the inpatient setting.…”
mentioning
confidence: 99%